Relasi Kekuasaan Dalam Film Uwais Al-Qarni Karya Akbar Tahvilian (Kajian Hegemoni Foucault) - Rika Rizki Rahayu; Fadlil Yani Ainusyamsi; Mawardi Mawardi; Yuke Alfi Zulyatmi (UIN Sunan Gunung Dajti Bandung, 2023)
This study explains the power relations carried out in the film Uwais al-Qarni by Akbar Tahvilian towards the woman Yathrib and the child character Salman. The Quraysh warriors exercised power relations with the Yathrib women through threatening words that made them hand over all the jewelry they had. Power relations are also carried out with a child named Salman. A Yemeni youth tries to bully Salman by abusing him. Literary research is a bridge of understanding between works and connoisseurs of works. This study aims to explain the forms of power relations action contained in the film Uwais Al-QarniKarya Akbar Tahvilian, which is then reviewed with Foucault's Hegemony. The method used in this research uses descriptive qualitative methods with a type of literary sociology approach, namely Foucault's hegemony. Research results from the film Uwais Al-Qarni show that the film contains various acts of nepotism committed by the authorities by fooling and oppressing the people, being arrogant, arrogant and pursuing popularity through the existence of power. While the form of power relations is carried out through thoughts in culture and religion, as well as social growth and development in the state and people.